Phenology and physiology of Brassica genotypes wth nitrogen levels on aridisols - KUMAR, ANIL; SINGH, D P; SINGH, BIKRAM; YADAV, YASH PAL (The Indian Journal of Agricultural Sciences, 2013)
The performance of 5 genotypes of Brassica juncea (L.) Czemj. & Coss.'CS 52','Kranti',' GJM 9056','RH 30'and 'RH 8814' and I genotype of Brassica napus L. 'GSH l' under 4 nitrogen levels were studied for two consecutiveseasons at Hisar to assess the effect of nitrogen fertilization on phenological and physiological behaviour of Brassicagenotypes. The flower initiation, full bloom, siliquae formation and 50 % pod browning were significantly delayed at80 kg N/ha compared to 40 kg N/ha in 'GJM 9056' genotype. The trend in other genotypes followed a descending order'RH 8814','CS 52','Kranti', 'RR 30','GSH I' in flower initiation and remained up to 50% pod browning. TheBrassica juncea genotypes had better physiological parameters viz leaf area index and crop growth rate compared withthe Brassica napus genotype. Leaf area index increased significantly with successive increase in N levels up to 60 kgN/ha while crop growth rate increased up to application of 80 kg N/ha.